Effects EFFECTS OF PUMPKIN (CUCURBITA MOSCHATA DURCH) SEED POWDER ON BLOOD GLUCOSE LEVEL IN STREPTOZOTOCIN-INDUCED MICE - NOVARIANTI MARBUN; RUTH MAYANA RUMANTI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this research is to evaluate the antidiabetic effect of pumpkin seed powder in streptozotocin (STZ)-induced diabetic mice. Methods: Pumpkin seed was used in seed powder suspension form and then evaluate the phytochemical screening and induced diabetic mice using STZ. Results: The phytochemical screening showed that pumpkin seed powder has various of phytochemical compounds. The pumpkin seed powder (dose level 100, 150, and 200 mg/kg bw) showed a significant reduction of blood glucose. Conclusions: Pumpkin seed powder significantly decreases blood glucose level in STZ-induced mice.